Effect of calcination temperature on (N, Fe) doped TiO2 nanoparticles - Ibrahim, Siti Aida; Zainal Alam, Abdul Hadi; Hussin, Rosniza; Kamdi, Zakiah; Mohamed Hatta, Mohamed Nasrul; Ainuddin, Ainun Rahmahwati; Yunos, Muhamad Zaini (UTHM Publisher, 2018)
TiO2 is one of the most promising photocatalysts that is widely used for environmental clean-up due to its ability to degrade organic pollutants in air or water in the presence of UV light irradiation. In this study, the sol-gel method followed by calcination process was employed to synthesize N, Fe doped TiO2 nanoparticles. The effect of calcination temperature on the structural, morphology and optical properties of the as-prepared samples was analyzed. Titanium tetra isopropoxide (TTIP) was used as Ti precursor and urea and ferric nitrate nonahydrate were the employed precursors to obtain N and Fe, respectively. X-ray diffraction pattern displayed a transformation of anatase structure to biphasic of anatase and rutile structure as the calcination temperature was increased from 300 to 700 °C. FESEM images indicated an agglomeration of particles with the grain size was estimated at 50-170 nm. UV-Vis analysis revealed that the increment of calcination temperature induced a red shift in the absorption spectra from 485 nm to 664 nm. Hence, the results indicate that N, Fe doped TiO2 is a highly potential visible-driven photocatalyst to degrade pollutants under the presence of visible light irradiation